2010
DOI: 10.1111/j.1551-2916.2010.03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Optical, and Magnetic Properties of Zn1−xCoxO Nanorods Grown via a Wet Chemical Route

Abstract: Co‐doped ZnO nanorods (Zn1−xCoxO) with x=0.05, 0.1, and 0.2 were successfully grown on indium‐doped tin oxide glass substrates via a wet chemical route at 70°C for 10 h. The effect of Co‐doping level on the morphology, crystalline phases, optical, and magnetic properties of the ZnO nanorods was studied. Based on scanning electron microscopy, TEM, and XRD studies, it is confirmed that Co‐doped ZnO nanorods were grown along the [0001] direction. Co doping affects the d‐spacing and with an increasing Co concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…18d). Mn doped and co-doped ZnO CSNS magnetization are comparable to those obtained for Mn and Co doped ZnO samples [19,77]. The magnetic moment of the of the ZnO: (Mn,Li) film is 0.18 µB/Mn and Zn 0.87 Mn 0.08 Li 0.05 O is 0.8 µB/Mn [37], which is higher than that of this work.…”
Section: Vsm Analysissupporting
confidence: 52%
“…18d). Mn doped and co-doped ZnO CSNS magnetization are comparable to those obtained for Mn and Co doped ZnO samples [19,77]. The magnetic moment of the of the ZnO: (Mn,Li) film is 0.18 µB/Mn and Zn 0.87 Mn 0.08 Li 0.05 O is 0.8 µB/Mn [37], which is higher than that of this work.…”
Section: Vsm Analysissupporting
confidence: 52%
“…61 Both intrinsic parameters like oxygen vacancy, Zn interstitial and extrinsic parameters like magnetic clusters or separate phase formation have been observed to be responsible for different kind of magnetic behaviour. [62][63][64][65] Several studies have reported on the grain boundary defect mediated ferromagnetism in Co-doped lms. [66][67][68][69] Recently, Aravindh et al predicted room temperature ferromagnetism arising due to exchange coupling of a pair of Co atoms at the grain boundary, a new observation based on rst-principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several reports on the synthesis of nanoparticles (NPs) by wet chemical route, there are very few reports on the formation of nanorods (NRs) without using any substrate/seed layer by this method. 55,60,65,77 The present study investigates the structural, optical and magnetic behavior of pure and Codoped ZnO NPs as well as NRs synthesized by a simple, lowcost chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt zinc (CoZn) ferrite ceramic has been the subject of numerous studies in the past years for its magnetic properties . The material is already used as permanent magnets or as granular magnetic recording media.…”
Section: Introductionmentioning
confidence: 99%
“…C OBALT zinc (CoZn) ferrite ceramic has been the subject of numerous studies in the past years for its magnetic properties. 1,2 The material is already used as permanent magnets or as granular magnetic recording media. Doping has also been performed on the CoZn ferrite to improve the saturation magnetization and coercivity.…”
Section: Introductionmentioning
confidence: 99%